2005
DOI: 10.1097/01.mib.0000186409.15392.54
|View full text |Cite
|
Sign up to set email alerts
|

Oral Medication Adherence in Pediatric Inflammatory Bowel Disease

Abstract: The purpose of this study was to examine reports of adherence to oral medications, parent-child concordance in reports of adherence, and factors associated with poor adherence in adolescents with inflammatory bowel disease (IBD). Participants were 50 children with IBD 11 to 17 years of age and their parents. Parents completed an adherence interview and the Child Behavior Checklist, Family Assessment Device, and demographics questionnaires. Separately, adolescents completed the adherence interview and the Piers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
3
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 28 publications
(59 reference statements)
4
107
3
5
Order By: Relevance
“…17 Thus, the patients labelled young adults herein are older than those reported in paediatric series. [19][20][21][22][23][24] As a result, we have intentionally drawn comparisons throughout this discussion from the adult literature with similar age ranges. Time constraints, medication side effects, poorly controlled disease activity and the perception that the drug is not working, as well as simply forgetting have been cited by young adults with IBD and their parents as reasons for non-adherence.…”
Section: External Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…17 Thus, the patients labelled young adults herein are older than those reported in paediatric series. [19][20][21][22][23][24] As a result, we have intentionally drawn comparisons throughout this discussion from the adult literature with similar age ranges. Time constraints, medication side effects, poorly controlled disease activity and the perception that the drug is not working, as well as simply forgetting have been cited by young adults with IBD and their parents as reasons for non-adherence.…”
Section: External Validitymentioning
confidence: 99%
“…17,18 The reasons for this have not been investigated, because the body of paediatric and/or adolescent literature has focused on children under the age of 17 years. [19][20][21][22][23][24] However, psychological co-morbidity has been implicated as a potentially reversible cause in children 24 and adults with IBD. 11,16,25,26 On the basis of our previous retrospective observations, 18 we hypothesised that non-adherence, objectively defined using thiopurine metabolite levels, is more common in young adults attending our adolescent transition clinic than adults with IBD and that psychological co-morbidity is a contributing factor.…”
Section: Introductionmentioning
confidence: 99%
“…Feelings ofhelplessness, dependency and low self-esteem, anxiety and depressive symptoms can have direct implications on adherence to treatment plans (Mackner & Crandall, 2006). Because these issues are associated with poor adherence, it has been suggested that psychotherapy addressing these areas may contribute to improved medication adherence (Mackner & Crandall, 2005). Given the significance of psychosocial issues associated with the disease and medication adherence among adolescents with ffiD, examination of non-adherence is likely best conceptualized with the BPS model.…”
Section: The Bio-psychosocial Modelmentioning
confidence: 99%
“…Given that non-adherence rates for maintenance medications in adolescentswith IBD range from 50% to 88% (Hommel et al, 2009;Mackner & Crandall, 2005;Oliva-Hemker at al., 2007) and its considerable impacts on health outcomes and healthcare costs, it is important for healthcare providers to understand the factors affecting adherence in adolescents with IBD and to develop and implement intervention strategies to promote medication adherence.…”
Section: Reducing Healthcare Costsmentioning
confidence: 99%
See 1 more Smart Citation